The Economic Impact of Cryptocurrencies in Indonesia (ADI Journal on Recent Innovation (AJRI), 2023)
In this era of global economic development, especially in Indonesia, it is inseparable from elements of high technology such as information. The development of information technology considers all fields, including the financial sector. Cryptocurrency, often called virtual/digital currency, results from the evolution of financial technology. Digital currency is widely used as a payment method on the Internet. This currency was created to provide convenience and security when making payments—with the included blockchain technology, reducing transaction costs. However, in this case, Bank Indonesia, the government has banned digital/cryptocurrency transactions because it hurts the Indonesian financial system, currency stability, and payment system. This study explains the impact of cryptocurrencies on the Indonesian economy and the government's attitude towards the technology it contains. In terms of the technology offered, cryptocurrency is an evolution of financial technology and will allow financial transactions to replace paper money with digital money in the future. The government will study more deeply the technology contained in cryptocurrencies. The policies made later will not prohibit the technology contained in cryptocurrencies. In general, it provides knowledge to gain a deeper understanding of cryptocurrencies. You will be able to do it.